2005
DOI: 10.1255/jnirs.459
|View full text |Cite
|
Sign up to set email alerts
|

Application of near Infrared Spectroscopy On-Combine in Corn Grain Breeding

Abstract: Improving maize (Zea mays L.) grain yield and agronomic properties are major goals for corn breeders in northern Europe. In order to facilitate fi eld grain yield determination we measured corn grain moisture content with near infrared (NIR) spectroscopy directly on a harvesting machine. NIR spectroscopy, in combination with harvesting, signifi cantly improved quality and speed of yield determination within the very narrow harvest time window. Moisture calibrations were developed with 2117 samples from the 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
3
13
0
Order By: Relevance
“…Significant differences for oil and moisture content were obtained between genotypes with similar grouping for both reference and NIR predicted results (Table 4). Moreover, the analysis of variance between and within genotypes provided similar distribution of sums of squares for reference and predicted data, which indicate that NIR predicted results could be efficiently used for genotype × environment and heritability studies as suggested in other crops (Welle et al, 2005;Posada et al, 2009). Models developed from samples collected in selections plots provided slightly more accurate results than the obtained in samples collected in progenies plots.…”
Section: Discussionmentioning
confidence: 62%
“…Significant differences for oil and moisture content were obtained between genotypes with similar grouping for both reference and NIR predicted results (Table 4). Moreover, the analysis of variance between and within genotypes provided similar distribution of sums of squares for reference and predicted data, which indicate that NIR predicted results could be efficiently used for genotype × environment and heritability studies as suggested in other crops (Welle et al, 2005;Posada et al, 2009). Models developed from samples collected in selections plots provided slightly more accurate results than the obtained in samples collected in progenies plots.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, calibration models for determination of dry mater, starch content, in vitro digestibility by cellulase, and soluble sugars in maize forage based on NIR measurements taken directly on the chopper during harvest were developed (Welle et al, 2003). Using a network of six diode arrays, NIR spectrometers were implemented successfully for on-line analysis of dry matter corn grain (Welle et al, 2005). With this method, calibration models were derived from the database of spectra from all six instruments; this eliminated the need to apply specific standardization algorithms when using different NIR instruments.…”
Section: Grain and Grain Productsmentioning
confidence: 99%
“…Therefore, DA-NIRS ensures greater accuracy and a short analysis time compared to conventional spectrometers. Although with these benefits, the scientific literature documenting the use of DA-NIRS for the compositional analysis of agricultural crops is limited Niewitetzki et al 2010;Welle et al 2005;Welle et al 2007).…”
Section: Effect Of Canola Seed Sample Size On Nir Analysismentioning
confidence: 99%